Development of high-throughput electron tomography for 3D morphological characterisation of soot nanoparticles - Haffner-Staton, Ephraim (2020)
In this work a methodology has been developed to permit high-throughput, high-quality morphology characterisation of soot nanoparticles in 3D, using transmission electron microscopy (TEM) and electron tomography (ET). Nanoparticle morphology plays an extremely important role in determining soots contribution to global climate change, its impacts on human health, and its relation to friction and wear in engines. Morphology characterisation is thus fundamental to enabling full understanding of soot-induced phenomena and subsequent strategies for their mitigation.